If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 163 + -1x + 101 + -1x = 126 Reorder the terms: 163 + 101 + -1x + -1x = 126 Combine like terms: 163 + 101 = 264 264 + -1x + -1x = 126 Combine like terms: -1x + -1x = -2x 264 + -2x = 126 Solving 264 + -2x = 126 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-264' to each side of the equation. 264 + -264 + -2x = 126 + -264 Combine like terms: 264 + -264 = 0 0 + -2x = 126 + -264 -2x = 126 + -264 Combine like terms: 126 + -264 = -138 -2x = -138 Divide each side by '-2'. x = 69 Simplifying x = 69
| 20x-5x^2=0 | | 12z+5=3z+41 | | 3b+4=b+8 | | 9(5h+5)=495 | | x(163+101)=126 | | .878=.5*9.8*t^2 | | -2+4=-3+11x | | 9z-40=3z-10 | | x-64=126 | | x+64=126 | | -7*0=-2+-7x | | 8z-3=2z+21 | | x-138=126 | | x+138=126 | | 5x+7=-33-5x | | x(138-x)=126 | | 5+8p=83 | | x+25=163 | | x-37=101 | | 4000=60000/t-11 | | x(-37)=101 | | x-37=126 | | x+25=126 | | 14x-2(-2+-7x)=4 | | x(64+x)=126 | | 2.5+14y=-3.1 | | 64-x=126 | | 3x+8=32-2x | | 62+x=126 | | 25+x+37-x=126 | | 61=-26y+22 | | 25(x+25)+37-x=126 |